Multimode interference wavelength multi/demultiplexer for 1310 and 1550 nm operation based on BCB 4024-40 photodefinable polymer - Ibrahim, Mohd Haniff; Lee, Shuh-Ying; Chin, Mee-Koy; Mohd Kassim, Norazan; Mohammad, Abu Bakar (Elsevier, 2007)
A 1310 and 1550 nm coarse wavelength multi/demultiplexer based on benzocyclobutene (BCB 4024-40) polymer is demonstrated for the first time. The device is designed based on a combination of general interference and paired interference mechanisms of multimode interference (MMI). It is fabricated on BK7 glass substrate with a thin layer of SiO2 as cover. A cost effective chemical etching technique is used in the fabrication process to take advantage of the photosensitive nature of the polymer. The device length was significantly reduced by adopting the restricted multimode interference scheme, lower beat length ratio and cascaded MMI couplers. The measured crosstalk at 1310 nm was 14.4 dB and at 1550 nm was 20.6 dB. The measured insertion loss is around 3.2–3.5 dB for both ports.